Peningkatan Pengetahuan Sanitasi dan Pola Hidup Bersih Melalui Kegiatan Sosialisasi - Wina Mustikaati; Adinda Dhea Pratiwi; Fairuz Andalusia; Syalsabila Eka Andini (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
School environment health and hygiene are crucial aspects for instilling healthy living habits from an early age. However, studies indicate that the level of understanding among primary school students regarding sanitation and Clean and Healthy Lifestyle (PHBS), especially handwashing practice, remains low. This research aims to describe the impact of implementing sanitation socialization based on practical activities for students at SDN 1 Nagri Kidul Purwakarta. The activities were conducted using a structured, demonstrative, and participatory educational approach, supported by the provision of portable handwashing facilities by UPI P3K students. This method placed the demonstration of correct handwashing steps as the central focus of the activity. The results show that the practical-based approach significantly improved students' understanding and skills, proving more effective than the lecture method. Students who initially only rinsed their hands are now able to correctly practice the steps of washing hands with soap, and they realize the importance of proper sanitation facilities. Thus, this socialization activity successfully cultivated the habit of correct handwashing, enhanced students' sanitation knowledge, and instilled an understanding of the necessity of adequate facilities. The sustainability of these positive habits requires facility support, ongoing guidance, and commitment from the school.